Transcription factors Sp1 and Sp4 regulate TRPV1 gene expression in rat sensory neurons - Eilers Helge; Xue Qing; Lee Jessica; Fahimi Atefeh; Zavala Kathryn; Chu Catherine; Schumacher Mark A (SAGE Publishing, 2011)
Abstract Background The capsaicin receptor, transient receptor potential vanilloid type -1 (TRPV1) directs complex roles in signal transduction including the detection of noxious stimuli arising from cellular injury and inflammation. Under pathophysiologic conditions, TRPV1 mRNA and receptor protein expression are elevated in dorsal root ganglion (DRG) neurons for weeks to months and is associated with hyperalgesia. Building on our previous isolation of a promoter system for the rat TRPV1 gene, we investigated the proximal TRPV1 P2-promoter by first identifying candidate Sp1-like transcription factors bound in vivo to the P2-promoter using chromatin immunoprecipitation (ChIP) assay. We then performed deletion analysis of GC-box binding sites, and quantified promoter activity under conditions of Sp1 / Sp4 over-expression versus inhibition/knockdown. mRNA encoding Sp1, Sp4 and TRPV1 were quantified by qRT-PCR under conditions of Sp1/Sp4 over-expression or siRNA mediated knockdown in cultured DRG neurons. Results Using ChIP analysis of DRG tissue, we demonstrated that Sp1 and Sp4 are bound to the candidate GC-box site region within the endogenous TRPV1 P2-promoter. Deletion of GC-box "a" or "a + b" within the P2- promoter resulted in a complete loss of transcriptional activity indicating that GC-box "a" was the critical site for promoter activation. Co-transfection of Sp1 increased P2-promoter activity in cultured DRG neurons whereas mithramycin-a, an inhibitor of Sp1-like function, dose dependently blocked NGF and Sp1-dependent promoter activity in PC12 cells. Co-transfection of siRNA directed against Sp1 or Sp4 decreased promoter activity in DRG neurons and NGF treated PC12 cells. Finally, electroporation of Sp1 or Sp4 cDNA into cultures of DRG neurons directed an increase in Sp1/Sp4 mRNA and importantly an increase in TRPV1 mRNA. Conversely, combined si-RNA directed knockdown of Sp1/Sp4 resulted in a decrease in TRPV1 mRNA. Conclusion Based on these studies, we now propose a model of TRPV1 expression that is dependent on Sp1-like transcription factors with Sp4 playing a predominant role in activating TRPV1 RNA transcription in DRG neurons. Given that increases of TRPV1 expression have been implicated in a wide range of pathophysiologic states including persistent painful conditions, blockade of Sp1-like transcription factors represents a novel direction in therapeutic strategies.